PENGEMBANGAN MEDIA INTERAKTIF HERAMA BERBASIS CANVA DENGAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR SISWA SD - Zharifah, Izdihar Afaf; Ika Ratnaningrum (Journal of Practice Learning and Educational Development, 2025)
This study confirmed that the development of HERAMA (Harmoni Ekosistem Rantai Makanan), an interactive learning media based on Canva and supported by the Quantum Teaching model, is highly feasible, practical, and effective for elementary school science learning. The validation results from material experts (91.6%) and media experts (91.2%) placed HERAMA in the “very valid” category, while students’ responses (≥95% positive) and teachers’ feedback indicated that the media was practical and engaging in classroom use. The effectiveness of HERAMA was strongly supported by statistical results, showing a significant increase in the mean score from 56.2 in the pretest to 85.4 in the posttest, with classical mastery improving from 16.7% to 91.7%. The N-Gain score of 0.738 further confirmed a high level of learning improvement. Compared with previous studies, this research not only supports earlier findings that interactive media and Quantum Teaching can enhance motivation and engagement but also provides new evidence on the quantitative effectiveness of Canva-based learning media for science concepts. HERAMA offers contextual, fun, and technology-oriented learning, aligned with the principles of the Merdeka Curriculum and the demands of 21st-century education. Therefore, HERAMA can serve as an innovative alternative for improving both motivation and conceptual understanding in IPAS, especially food chain learning.